Mouse GATA-4: a retinoic acid-inducible GATA-binding transcription factor expressed in endodermally derived tissues and heart. - Arceci, R J (1993)
We report the cDNA cloning and characterization of mouse GATA-4, a new member of the family of zinc finger transcription factors that bind a core GATA motif. GATA-4 cDNA was identified by screening a 6.5-day mouse embryo library with oligonucleotide probes corresponding to a highly conserved region of the finger domains. Like other proteins of the family, GATA-4 is approximately 50 kDa in size and contains two zinc finger domains of the form C-X-N-C-(X17)-C-N-X-C. Cotransfection assays in heterologous cells demonstrate that GATA-4 trans activates reporter constructs containing GATA promoter elements. Northern (RNA) analysis and in situ hybridization show that GATA-4 mRNA is expressed in the heart, intestinal epithelium, primitive endoderm, and gonads. Retinoic acid-induced differentiation of mouse F9 cells into visceral or parietal endoderm is accompanied by increased expression of GATA-4 mRNA and protein. In vitro differentiation of embryonic stem cells into embryoid bodies is also associated with increased GATA-4 expression. We conclude that GATA-4 is a tissue-specific, retinoic acid-inducible, and developmentally regulated transcription factor. On the basis of its tissue distribution, we speculate that GATA-4 plays a role in gene expression in the heart, intestinal epithelium, primitive endoderm, and gonads.